PROFIT MAXIMIZING BUNDA BAKERY USING SIMPLEX METHOD - Budiyanto Budiyanto; Sigit Mujiharjo; Siti Umroh (BPFP Faperta UNIB, 2017)
Bunda Bakery is currently produce 19 various bread products weekly with using certain amout of various materials, and utilizing machine and labours. However, the optimal product and potencial profit of the bread production had not been determined. The Objective of the studywere toevaluate and optimize the bread production and its potencial profit. Simplex method,one of the techniques used in linear programming,was utilized to find the optimal valuethat involves many variables in the study. Previous record of each kind bread products were used to optimize various bread had to be produced and the potential profit to be gained Machine and labor utilization were further employed to use up the weekly raw material for optimizing the total bread product can be produced and the potential profits to be gained. The results indicate that before optimization, available raw matrials can beused to produce 676 unit products with potencial profit of 1,663,914 IDR in one week production.Optimization of raw materials could produce 697 unit products with potencial profit of 1,943,489 IDR in the same period of production. In addition, further optimization of production resources (material, labor and machine utilization) to used up the whole weekly materials, with additional selected materials, Bunda bakery could produce 1050 unit products with potencial profit of 2,286,049 IDR in one week production.